Exploring Challenges EFL Pre-Service Teachers Experience in Teaching Practicum: A Transformative Learning Perspective - Feni Maharani; Rahmah Fithriani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This study examines pre-service teachers' experience, especially on challenges they face through transformative learning. Qualitative descriptive research was utilized as a research methodology to explore the teachers’ experience during teaching practicum. Five seventh semester students of English education department were invited to be the participants of the study. The data were collected through reflective notes and in-depth interviews and then analyzed thematically. The results show that the pre-service teachers confront several obstacles throughout their teaching practicum. According to the data, the obstacles pre-service experienced were a Tension between vision and reality, teaching practicum, which is accompanied by class lectures, classroom management, and lack of supervision. The obstacles are then explored via transformational learning, which enables teachers to overcome them, particularly in classroom management, enhancing their capacity to choose teaching techniques depending on the needs and skills of students. This study is hoped the difficulties during teaching practicum faced by pre-service teachers can be reduced so that the objectives of teaching practicum can be achieved properly.